1998
DOI: 10.1159/000045164
|View full text |Cite
|
Sign up to set email alerts
|

Apo(a) Phenotypes and Lp(a) Concentrations in Renal Transplant Patients

Abstract: Plasma lipoprotein (a) (LP(a)) concentrations are increased in patients with end-stage renal disease. Considering the influence of the apolipoprotein (a) (Apo(a)) polymorphism and the mode of dialysis in this prospective longitudinal study, we compared Lp(a) concentrations before and after the first 6 months of a successful kidney transplantation in 125 recipient patients. Apo(a) phenotyping was performed by using SDS-PAGE and SDS-agarose, isoforms were classified into high molecular weight (HMW) and low molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2000
2000
2004
2004

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Apo(a) isoform sizes were determined by comparison of their sizes with an apo(a) standard (Immuno-AG) electrophoresed on each gel which contained 5 different isoforms. Low molecular weight (LMW) apo(a) phenotypes included all subjects who had at least one of the isoforms F, B, S1 or S2, whereas the high molecular weight (HMW) apo(a) phenotypes included all subjects with only S3 or S4 isoforms or with null type [21,25,26]. …”
Section: Methodsmentioning
confidence: 99%
“…Apo(a) isoform sizes were determined by comparison of their sizes with an apo(a) standard (Immuno-AG) electrophoresed on each gel which contained 5 different isoforms. Low molecular weight (LMW) apo(a) phenotypes included all subjects who had at least one of the isoforms F, B, S1 or S2, whereas the high molecular weight (HMW) apo(a) phenotypes included all subjects with only S3 or S4 isoforms or with null type [21,25,26]. …”
Section: Methodsmentioning
confidence: 99%
“…Kandoussi et al (22) reported that successful transplantation leads rapidly to a correction of Lp(a), probably in relation to the improvement of the renal function, suggesting an active role of the kidney in Lp(a) metabolism. In healthy people the serum level of Lp(a) has been shown to depend basically on its hepatic synthesis (8,23).…”
Section: Parametersmentioning
confidence: 99%
“…In CRF patients an accumulation of Lp(a) fragments or a reduction in their metabolism might occur (8,26). The most important factor seems to be the low molecular weight status corresponding to high Lp(a) levels (22). The kidney may influence the Lp(a) metabolism through either secretion of a factor that regulates Lp(a) synthesis (27) or the presence of uremic toxins that can influence regulatory mechanism synthesis and /or the catabolic pathways (6).…”
Section: Parametersmentioning
confidence: 99%
“…Plasma Lp(a) concentrations usually increase in patients with severe end-stage renal disease but, although it is known that Lp(a) levels in patients with chronic renal failure are higher than in normal controls, the precise mechanism underlying this phenomenon is unclear (17). A successful transplantation corrects Lp(a) levels probably as a result of improved renal function, thus suggesting that the kidney plays an active role in Lp(a) metabolism (17)(18)(19)(20). rhGH may be used to help growth-retarded children after renal transplant (21)(22)(23)(24)(25)(26)(27)(28)(29)(30), and growth hormone is important in the regulation of fat metabolism (31)(32)(33).…”
Section: Introductionmentioning
confidence: 99%